Book Review - Cohen, Benjamin J. ; Gwyn, Richard; Johnson, R.W.; Hersh, Seymour (Tufts Archival Research Center, 2005)
Volume 11, Issue 1. Winter. In Whose Interest? International Banking and American Foreign Policy. The 49th Paradox: Canada in North America. Shootdown: Flight 007 and the American Connection. The Target Is Destroyed. Book Review